Stunting Management: A Systematic Review - Sayekti, Essy Sonontiko; Ardiana, Anisah; Susanto, Tantut (Nursing Information Journal, 2025)
Stunting is a global problem, especially in developing countries. The management of stunting involves the cooperation of various parties and several factors that are carried out to overcome and prevent stunting because of its impact on hindering cognitive and productivity of children in the future. This study was designed to determine the management of handling children with stunting. This research method is a systematic literature review using 4 electronic databases namely PubMed, Google Scholar, Sciencedirect, and ProQuest. Articles containing stunting management strategy were analyzed using the PRISMA method. There were 15 articles met the criteria based on PRISMA analysis, emphasizing 7 strategies in the management of stunted children, namely fulfilling child nutrition, breastfeeding and colustrum, government policies, health promotion, maternal mental health, home visits (mentoring) and environmental sanitation.The main management of stunting is the maternal factor, starting from the fulfillment of nutrition during pregnancy period, breastfeeding to maternal mental health to provide good parenting. Cross-sectoral cooperation from the government and community support is also required to help care for children with stunting.